La República Popular de China y Australia: ¿fin a años de tensiones? - ROMÁN GONZÁLEZ, Mónica (Journal of the Spanish Institute for Strategic Studies, 2024)
Australia is a country which faces a complex situation from the point of view of world geopolitics, as it maintains an economic and trade dependence on China while is also aligned with the United States on security issues. For this reason, Canberra’s strategy has been based on trying to balance its trade relationship with Beijing with the strengthening of its defence alliance with Washington. Despite this, Sino-Australian relations have deteriorated dramatically with accusations and doubts raised about government policies on both sides in recent years. This resulted in China’s imposition of trade restrictions on Australian key exports and in a diplomatic freeze between both countries that has now ended after several years. However, a wide variety of factors have contributed to the stabilisation of the situation between the actors involved, as demonstrated by the meeting between Anthony Albanese and Xi Jinping on November 6, 2023.